Clinical Characteristics, Pathophysiology, and Management of Noncentral Nervous System Cancer-Related Cognitive Impairment in Adults - Wefel, Jeffrey S. (CA Cancer J Clin, 2014)
Over the past few decades, a body of research has emerged confirming what many adult patients with noncentral nervous system cancer have long reported—that cancer and its treatment are frequently associated with cancer-related cognitive impairment (CRCI). The severity of CRCI varies, and symptoms can emerge early or late in the disease course. Nonetheless, CRCI is typically mild to moderate in nature and primarily involves the domains of memory, attention, executive functioning, and processing speed. Animal models and novel neuroimaging techniques have begun to unravel the pathophysiologic mechanisms underlying CRCI, including the role of inflammatory cascades, direct neurotoxic effects, damage to progenitor cells, white matter abnormalities, and reduced functional connectivity, among others. Given the paucity of research on CRCI with other cancer populations, this review synthesizes the current literature with a deliberate focus on CRCI within the context of breast cancer. A hypothetical case-study approach is used to illustrate how CRCI often presents clinically and how current science can inform practice. While the literature regarding intervention for CRCI is nascent, behavioral and pharmacologic approaches are discussed.